A phenomenological investigation into lecturers' understanding of themselves as assessors at Rhodes University - Grant, Rosemary (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2005)
This thesis sets out to obtain an understanding of what it means to be an assessor in higher education, more especially within the Rhodes University context. The concept of assessment, a highly contentious and complex issue, is examined against a background of competing understandings of the nature and purpose of higher education, including the striving for excellence versus the call to more equitable ideals associated with a mass higher education and training system. An overview of salient issues is presented in which both traditional and alternative paradigms of measurement and assessment theory are explored with a view to considering foundational principles upon which sound assessment practice should be based. Specific methods and instruments of assessment are examined with the purpose of evaluating their potential for empowering students as active participants in their own learning and in the assessment process. In a field in which much of the literature seeks improved assessment merely through the administration of increasingly sophisticated assessment techniques, a phenomenological investigation offered a unique way of understanding the meaning assessors make of their practice. Making use of in-depth interviews with five lecturers at Rhodes University the researcher, interacting in a personal manner with people not viewed as experimental objects but as human subjects, assisted participants in moving towards non-theoretical descriptions that accurately reflected their experience. Insights contained in the data were synthesised and integrated into a consistent description of the essential nature of the experience, the primary endeavour of the phenomenologist being to transform naïve experience into more explicitly detailed conceptual knowledge. The essence of how these educators understand themselves as assessors at Rhodes University is perhaps best encapsulated by a considerable sense of agency or initiative on their part. While participants make use of a variety of assessment strategies, they are conscious that assessment cannot be viewed in isolation from other aspects of their teaching and the curriculum. Not only do they make use of different assessment methods but, conscious of accommodating the diverse needs of students, understand their responsibility in terms of providing learning opportunities to assist students in meeting the course outcomes and fulfilling their potential. Rather than allowing pressures from within and outside of the academy to dictate, these lecturers, with significant hard work, courage and a capacity for reflective practice, have embraced the challenges associated with higher education in a state of transition.
Keywords: Curriculum-based assessment -- South Africa; Education, Higher -- South Africa -- Evaluation; Educational tests and measurements -- South Africa; Education, Higher -- Evaluation -- Case studies; Universities and colleges -- South Africa